Nanolipsome Modified with Inulin and Pea Protein Isolate Improve the Thermal Stability and Slow the Release of Anthocyanin at Simulated In Vitro Digestion and Hot Cocoa Beverage - Aniya; Lianlian Zhang; Yan Li; Xiaoji Fu (Foods)
Anthocyanin (ACN) is a natural pigment with various biological activities, but their stability is compromised by external environmental factors, which limits their practical application in food processing. To enhance the stability of anthocyanin, double-layer-modified anthocyanin nanoliposomes (ACN-NLs) were prepared in this study using pea protein isolate (PPI) and inulin (IN) through layer-by-layer assembly in this study. The preparation conditions of unmodified, single-modified, and double-layer-modified nanoliposomes (ACN-NLs, PPI-ACN-NLs, and IN-PPI-ACN-NLs) were optimized via analysis of their average particle size, zeta potential, and encapsulation efficiency (EE). In addition, the structure of the nanoliposomes was characterized via transmission electron microscopy (TEM) and a Fourier transform infrared (FTIR) spectrometer. Furthermore, the thermal stability of nanoliposomes in hot cocoa and their release behavior during in vitro simulated digestion were evaluated. The results indicated that the optimal formulation for IN-PPI-ACN-NLs was 6% PPI and 2% IN. Under these conditions, the IN-PPI-ACN-NLs had a particle size of 270.2 ± 0.66 nm, a zeta potential of −15.76 ± 0.81 mV, and a high EE of 88.6 ± 0.71%. TEM analysis revealed that IN-PPI-ACN-NLs exhibited a spherical core–shell structure, while FTIR confirmed the interaction between ACNs and the encapsulating materials (PPI and IN). Compared with unmodified or monolayer-modified nanoliposomes, IN-PPI-ACN-NLs exhibited thermal stability in beverage systems and enhanced DPPH radical scavenging activity. During in vitro digestion, IN-PPI-ACN-NLs demonstrated a sustained-release effect and improved the digestive stability of ACN. These properties make it a promising functional additive for applications in the food and pharmaceutical industry.